A kind of ferromanganese phosphate precursor, ferromanganese phosphate lithium positive electrode material and preparation method thereof

By using modified hollow carbon microspheres to fix manganese ions and iron ions, and introducing thiol groups on the surface to maintain the divalent state of manganese ions, the problems of low electronic conductivity and slow lithium ions diffusion rate of the lithium manganese ferrophosphate cathode material are solved, and the circulation performance and conductivity of the material are significantly improved.

CN119218964BActive Publication Date: 2025-03-25HUNAN YUNENG NEW ENERGY BATTERY MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411718560.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-25
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

Lithium manganese iron phosphate positive electrode materials have problems such as low electronic conductivity and slow lithium ion diffusion rate, which leads to difficult release of high potential platform capacity, and the valence distortion of manganese and crystal structure distortion, affecting the safety and electrochemical properties of the material.

Method used

Modified hollow carbon microspheres are used as the carrier of ferromanganese phosphate. Manganese ions and ferromones are fixed in the hollow structure through electrostatic adsorption and capillary action to form ferromanganese phosphate, and thiol groups are introduced on the surface to maintain the divalent state of manganese ions, reducing manganese dissolution and lattice distortion.

Benefits of technology

The cycling and conductivity of lithium manganese iron phosphate cathode material is improved, the dissolution of manganese and crystal structure are reduced, and the stability and electrochemical properties of the material are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a ferromanganese phosphate precursor, a lithium ferromanganese phosphate positive electrode material and a preparation method thereof, and belongs to the technical field of lithium ion batteries. In the preparation process of the ferromanganese phosphate precursor, modified hollow carbon microspheres are added, which can protect and fix manganese ions and iron ions, and can also form a three-dimensional conductive network, improve the diffusion rate of lithium ions and the transmission speed of free electrons, and improve the conductivity of the material; and then the modified hollow carbon microspheres loaded with ferromanganese phosphate are coated by adding an iron source, so as to better ensure that manganese is not easy to dissolve during the charge and discharge process, and avoid causing lattice distortion of the positive electrode material. And the surface of the modified hollow carbon microspheres used in the present invention also contains a thiol group, which can reduce and keep manganese ions and iron ions in a stable divalent state, increase compatibility, reduce the content of trivalent manganese ions, thereby reducing the probability of lattice distortion, thereby improving the cycle performance and electrochemical performance of the positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a manganese iron phosphate precursor, a manganese iron phosphate lithium positive electrode material and a preparation method thereof. Background Art

[0002] Among the positive electrode materials of lithium-ion batteries, lithium iron phosphate positive electrode materials are widely used due to their excellent safety performance and low cost, but lithium iron phosphate has low energy density and small actual specific capacity; while lithium manganese phosphate, which is also a phosphate positive electrode material, has the same theoretical specific capacity and a higher voltage platform, but its electronic conductivity is poor. As a new type of phosphate positive electrode material, lithium manganese iron phosphate combines the excellent thermal stability and cycle performance of lithium iron phosphate positive electrode materials with the advantages of high voltage platform and good low temperature performance of lithium manganese phosphate, becoming one of the most promising lithium-ion battery positive electrode materials.

[0003] However, lithium iron manganese phosphate cathode materials still have the problems of low electronic conductivity and slow lithium ion diffusion rate. These problems make it difficult to release the high potential platform capacity of lithium iron manganese phosphate cathode materials. The disproportionation of manganese valence will further cause the crystal structure of lithium iron manganese phosphate to be distorted, thereby causing manganese to dissolve, affecting the safety and electrochemical properties of the material. In addition, the distortion of the crystal structure is not conducive to the deintercalation of lithium ions, resulting in a significant decrease in the cycle performance and specific capacity of lithium iron manganese phosphate cathode materials. Summary of the invention

[0004] The object of the present invention is to provide a manganese iron phosphate precursor, a lithium iron manganese phosphate positive electrode material and a preparation method thereof, so as to solve the problems of dissolution of lithium iron manganese phosphate and poor cycle performance.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] In a first aspect, the present invention provides a method for preparing a ferromanganese phosphate precursor, comprising the following process steps:

[0007] S101. Adding a phosphorus source, a manganese source and a portion of an iron source to deionized water to prepare a premix, wherein the portion of the iron source is 50 to 60% of the total mass of the iron source;

[0008] S102. Adding modified hollow carbon microspheres and a dispersant to the premixed solution, raising the temperature to 70 to 80° C., stirring the reaction for 4 to 6 hours, filtering, washing and drying to obtain a pre-reactant;

[0009] S103. The pre-reactant is dispersed in deionized water, the remaining iron source is added, the temperature is raised to 60 to 70 ° C in a nitrogen atmosphere, stirred and mixed for 2 to 3 hours, and then washed, dried and calcined to obtain a manganese iron phosphate precursor;

[0010] The surface of the modified hollow carbon microspheres contains mercapto groups.

[0011] Preferably, the molar ratio of the phosphorus source, the manganese source and the iron source is 1:(0.3-0.5):(0.5-0.7).

[0012] Preferably, the added amount of the modified hollow carbon microspheres is 10-20% of the total mass of the phosphorus source, the manganese source and the iron source.

[0013] Preferably, the phosphorus source includes one or more combinations of phosphorus pentoxide, phosphoric acid, lithium dihydrogen phosphate, lithium hydrogen phosphate, sodium phosphate, potassium phosphate, pyrophosphoric acid, diammonium hydrogen phosphate and ammonium dihydrogen phosphate.

[0014] Preferably, the manganese source comprises a combination of one or more of manganese sulfate, manganese carbonate, manganese oxalate, manganese phosphate, manganous chloride, manganous bromide, manganous nitrate and manganous acetate.

[0015] Preferably, the iron source includes one or more combinations of ferric nitrate, ferric carbonate, ferric phosphate, ferric chloride, iron powder, ferric oxide, ferrous nitrate, ferrous sulfite and ferrous acetate.

[0016] Preferably, the dispersant includes a combination of one or more of citric acid, succinic acid, tripropyl phosphate, dibutyl phosphate, methylcyclosiloxane, sodium dodecylbenzene sulfonate and sodium octylbenzene sulfonate; the added amount of the dispersant is 3 to 6% of the total mass of the phosphorus source, manganese source and iron source.

[0017] Preferably, the solid content of the premix is ​​40-50%.

[0018] Preferably, the calcination temperature is 250-400°C.

[0019] By adopting the above technical scheme, in the preparation process of the ferromanganese phosphate precursor of the present invention, firstly, the manganese source, the phosphorus source and part of the iron source are reacted on the modified hollow carbon microspheres, and ferromanganese phosphate is formed in the hollow pores inside the modified hollow carbon microspheres, and the manganese source reacts completely. Due to the excessive amount of added phosphorus source, the excess phosphorus source will be adsorbed and loaded on the surface of the hollow carbon microspheres, and further continue to react with the remaining iron source, and gradually coat a layer of ferrophosphate on the surface of the modified hollow carbon microspheres. Since the ferromanganese phosphate precursor obtained in this way is coated with ferrophosphate on the outside, the manganese ions inside will not directly contact the electrolyte, thereby reducing the possibility of valence disproportionation of manganese, thereby reducing the distortion of the material grain structure and the dissolution of manganese.

[0020] The present invention uses modified hollow carbon microspheres as carriers for loading ferromanganese phosphate, which can fix manganese ions and iron ions on the one hand. Since the hollow carbon microspheres have a unique porous hollow shell structure, in step S102, manganese ions and iron ions can be attracted into their internal hollow structure through electrostatic adsorption, capillary action and various intermolecular forces, and gradually form ferromanganese phosphate, and the fixed manganese ions are not easy to be separated from the electrolyte, thereby reducing the dissolution of manganese. At the same time, the hollow carbon microspheres can also improve the interface stability between the positive electrode material and the electrolyte, reduce the direct contact of the electrolyte with the surface of the positive electrode material, suppress the occurrence of side reactions, effectively avoid the defects generated after the dissolution of manganese, and then coat with iron phosphate to further reduce the dissolution of manganese, thereby improving the cycle performance of the lithium ferromanganese phosphate positive electrode material.

[0021] On the other hand, hollow carbon microspheres can serve as the carbon skeleton of the ferromanganese phosphate precursor, providing mechanical support for the precursor and improving the stability of the material. Moreover, since the hollow carbon microspheres have a three-dimensional structure, they can form a continuous three-dimensional conductive network in the material, providing more free electron transmission paths, shortening the transmission distance of electrons and lithium ions, maintaining a good transmission path, and can also enhance the correlation between ferromanganese phosphate precursor particles, increase the contact area between particles, and reduce contact resistance, thereby further improving the conductivity of the positive electrode material.

[0022] Furthermore, the hollow carbon microspheres are modified to introduce thiol groups on their surfaces. These thiol groups can reduce the manganese ions and iron ions in the system and keep them in a stable divalent state. Since divalent manganese ions and divalent iron ions have similar ionic radii, they can be infinitely dissolved, thereby ensuring that the compatibility problem during subsequent iron phosphate coating is solved, and the inner and outer layers can be well combined to maintain the integrity of the structure; and through the action of thiol groups, the probability of trivalent manganese ions in the system is greatly reduced. Trivalent manganese ions are one of the main causes of lattice distortion, which will lead to poor solid solubility between manganese and iron phosphate in the material, reduce structural stability, and increase the probability of manganese dissolution. Converting manganese ions to a stable divalent state can not only give full play to the respective advantages of manganese ions and iron ions, but also significantly improve the cycle performance and electrochemical performance of the positive electrode material.

[0023] Preferably, the raw materials for modifying hollow carbon microspheres include hollow carbon microspheres, pyrrole monomers and mercapto acid in a mass ratio of 1: (0.3-0.5): (0.05-0.1).

[0024] Preferably, the mercapto acid comprises a combination of one or more of thioglycolic acid, mercaptopropionic acid and 6-mercaptohexanoic acid.

[0025] Preferably, the hollow carbon microspheres are prepared according to the following method:

[0026] Styrene and acrylic acid monomers are added to water, mixed evenly, and then the temperature is raised to 70-80°C under a nitrogen atmosphere, an initiator is added, and the mixture is stirred for reaction for 12-24 hours, followed by centrifugation, washing and drying to obtain polystyrene microspheres; polystyrene microspheres are dispersed in anhydrous ethanol, tetraethyl orthosilicate is added, the temperature is raised to 40-50°C, ammonia water is added dropwise, the mixture is stirred for reaction for 10-12 hours, and then the mixture is allowed to stand for separation and dried to obtain polystyrene-silica microspheres;

[0027] The obtained polystyrene-silica microspheres are carbonized at 700-800°C in a nitrogen atmosphere for 2-3 hours, then added to a hydrofluoric acid solution with a mass fraction of 10-20%, mixed evenly, and etched for 12-24 hours. Then, hollow carbon microspheres are obtained by centrifugation, washing and drying.

[0028] More preferably, the acrylic monomer includes a combination of one or more of acrylic acid, methyl methacrylate, ethyl acrylate and butyl acrylate; the mass ratio of styrene to acrylic monomer is 1:(0.03-0.06);

[0029] More preferably, the initiator includes a combination of one or more of potassium persulfate, ammonium persulfate, sodium persulfate, and lithium persulfate; the amount of the initiator added is 0.5 to 1.5% of the mass of styrene;

[0030] More preferably, the mass ratio of polystyrene microspheres to tetraethyl orthosilicate is 1:(0.04-0.08);

[0031] More preferably, the mass ratio of polystyrene microspheres to ammonia water is 1:(0.1-0.3).

[0032] Preferably, the modified hollow carbon microspheres are prepared according to the following method: hollow carbon microspheres are added to a solvent, the pH value of the solution is adjusted to 2-3, and after uniform dispersion, pyrrole monomer and mercapto acid are added, and the mixture is stirred at 0-25°C, an initiator is added, and the reaction is continued by stirring for 6-8h, and then vacuum filtration, washing and drying are performed to obtain the modified hollow carbon microspheres.

[0033] Preferably, the solvent includes a combination of one or more of water, ethanol aqueous solution and N,N-dimethylformamide.

[0034] Preferably, the initiator includes a combination of one or more of potassium persulfate, ammonium persulfate, sodium persulfate, and lithium persulfate; and the added amount of the initiator is 0.15 to 0.25 mol / L.

[0035] By adopting the above technical solution, polystyrene microspheres are used as templates, combined with silica, and the silica is removed by etching after carbonization to form hollow carbon microspheres with a hollow porous structure, which provide a protective space for manganese ions and iron ions to form manganese iron phosphate precursors.

[0036] The hollow carbon microspheres are modified by introducing thiol groups on the surface of the hollow carbon microspheres through chemical bonding between thiol acid and the hollow carbon microspheres, so as to maintain the uniformity of the valence states of manganese ions and iron ions in the manganese iron phosphate precursor and reduce the influence of trivalent manganese ions on lattice distortion.

[0037] At the same time, in order to enhance the attraction of hollow carbon microspheres to manganese ions and iron ions, so that the manganese ions and iron ions in the system can smoothly enter the interior of the hollow carbon microspheres or the surface pores, a layer of polypyrrole is also deposited on the surface of the hollow carbon microspheres, which can enhance the attraction to metal ions while allowing metal complexation with manganese ions and iron ions to occur, thereby enhancing the binding force of manganese ions and iron ions on the hollow carbon microspheres and enhancing the reduction effect of thiol groups on manganese ions and iron ions. In addition, after calcination, polypyrrole can be used to reinforce the skeleton structure of hollow carbon microspheres, improve the structural stability of the manganese iron phosphate precursor, and thus improve the electrochemical performance of the positive electrode material.

[0038] In a second aspect, the present invention provides a ferromanganese phosphate precursor prepared according to the above-mentioned method for preparing the ferromanganese phosphate precursor.

[0039] In a third aspect, the present invention provides a method for preparing a lithium iron manganese phosphate positive electrode material, comprising the following process steps:

[0040] S201. The ferromanganese phosphate precursor, lithium source and carbon source obtained above are mixed and configured into a slurry with deionized water;

[0041] S202. Grind and spray-dry the obtained slurry, then sinter at a high temperature of 600-800° C., and finally crush to obtain lithium manganese iron phosphate positive electrode material.

[0042] Preferably, the molar ratio of the lithium source to the phosphorus source in step S101 is (0.95-1.1):1; and the amount of the carbon source added is 5-10% of the mass of the ferromanganese phosphate precursor.

[0043] Preferably, the lithium source includes one or more combinations of lithium hydroxide, lithium dihydrogen phosphate, lithium acetate, lithium bromide, lithium chlorate, lithium chloride, lithium fluoride, lithium fluorosilicate, lithium formate, lithium iodide, lithium nitrate and lithium carbonate.

[0044] Preferably, the carbon source comprises one or more combinations of glucose, sucrose, lactose, citric acid, sodium acetate, polyethylene glycol, polyethylene diene and carbon nanotubes.

[0045] By adopting the above technical solution, the modified hollow carbon microspheres are used as carriers in the ferromanganese phosphate precursor, and the original one-dimensional lithium ion diffusion channel can be transformed into a three-dimensional lithium ion diffusion channel, thereby improving the efficiency of lithium ion deintercalation, thereby increasing the rate performance of the positive electrode material. Coating a layer of carbon on the outside of the lithium ferromanganese phosphate positive electrode material can provide a more complete electron transmission path and lithium ion diffusion channel for the positive electrode material, and can cooperate with the carbon skeleton in the precursor to improve the bonding force between the carbon-coated positive electrode materials, thereby improving the conductivity of the positive electrode material.

[0046] In a fourth aspect, the present invention provides a lithium iron manganese phosphate positive electrode material, which is prepared according to the above-mentioned method for preparing the lithium iron manganese phosphate positive electrode material.

[0047] Beneficial effects of the present invention:

[0048] 1. The ferromanganese phosphate precursor of the present invention introduces modified hollow carbon microspheres during the preparation process to fix manganese ions and iron ions. The hollow shell structure can protect manganese ions and iron ions from being easily removed from the electrolyte, thereby avoiding valence disproportionation after manganese ions are removed to cause lattice distortion. After manganese ions and iron ions form ferromanganese phosphate inside the hollow carbon microspheres, the remaining iron source is added. At this time, the excess phosphorus ions on the surface of the hollow carbon microspheres will react with the iron source to form an iron phosphate coating on the surface of the hollow carbon microspheres, further reducing the dissolution of manganese and improving the cycle performance of the material. At the same time, the hollow carbon microspheres can provide mechanical support for the precursor, improve the stability of the material structure, and can form a three-dimensional conductive network to improve the conductivity of the positive electrode material.

[0049] 2. The hollow carbon microspheres used in the present invention are also modified by introducing thiol groups on the surface to reduce and maintain manganese ions and iron ions in a stable divalent state, thereby greatly reducing the presence of trivalent manganese ions and the dissolution of manganese while improving compatibility, thereby reducing the probability of lattice distortion of the positive electrode material; and during the modification process, a layer of polypyrrole is deposited on the surface of the hollow carbon microspheres, which can increase the attraction and binding force to metal ions, strengthen the skeleton structure of the hollow carbon microspheres, and improve the electrochemical properties of the material. DETAILED DESCRIPTION

[0050] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0051] Preparation Example

[0052] Preparation Example 1: A modified hollow carbon microsphere is prepared according to the following method:

[0053] 10 g of styrene and 0.5 g of methyl methacrylate were added to water, mixed evenly, and then the temperature was raised to 80°C under a nitrogen atmosphere, 0.1 g of potassium persulfate was added, and the mixture was stirred for 14 h, followed by centrifugation, washing and drying to obtain polystyrene microspheres; 10 g of polystyrene microspheres were dispersed in 250 mL of anhydrous ethanol, 0.6 g of tetraethyl orthosilicate was added, the temperature was raised to 45°C, 2 g of ammonia water was added dropwise, the mixture was stirred for 12 h, and then the mixture was allowed to stand for separation and dried to obtain polystyrene-silica microspheres;

[0054] The obtained polystyrene-silica microspheres were carbonized at 800°C for 2 h in a nitrogen atmosphere, then added to 100 mL of a 15% hydrofluoric acid solution, mixed evenly, and etched for 12 h. The hollow carbon microspheres were then obtained by centrifugation, washing, and drying.

[0055] 10 g of hollow carbon microspheres were added to 250 mL of 50% ethanol aqueous solution, the pH value of the solution was adjusted to 3, and after uniform dispersion, 4 g of pyrrole monomer and 0.8 g of thioglycolic acid were added, and the mixture was stirred at 10 °C. 0.2 mol / L sodium persulfate was added, and the reaction was continued by stirring for 8 h. Then, the modified hollow carbon microspheres were obtained by vacuum filtration, washing and drying.

[0056] Preparation Example 2, a modified hollow carbon microsphere, is different from Preparation Example 1 only in that the added amount of pyrrole monomer is 3 g and the added amount of thioglycolic acid is 0.5 g.

[0057] Preparation Example 3, a modified hollow carbon microsphere, is different from Preparation Example 1 only in that the added amount of pyrrole monomer is 5 g and the added amount of thioglycolic acid is 1 g.

[0058] Preparation Example 4, a modified hollow carbon microsphere, is different from Preparation Example 1 only in that the amount of thioglycolic acid added is 0.3 g.

[0059] Preparation Example 5, a modified hollow carbon microsphere, is different from Preparation Example 1 only in that the amount of thioglycolic acid added is 1.2 g.

[0060] Preparation Example 6, a modified hollow carbon microsphere, is different from Preparation Example 1 only in that the hollow carbon microsphere is modified according to the following method:

[0061] 10 g of hollow carbon microspheres were added to 250 mL of 50% ethanol aqueous solution, the pH value of the solution was adjusted to 2, and after uniform dispersion, 0.8 g of thioglycolic acid was added, and the reaction was stirred at 25°C for 6 h, and then vacuum filtered, washed and dried to obtain modified hollow carbon microspheres.

[0062] Preparation Example 7, a modified hollow carbon microsphere, is different from Preparation Example 1 only in that no thioglycolic acid is added.

[0063] Preparation Example 8, a hollow carbon microsphere, is different from Preparation Example 1 only in that the obtained hollow carbon microsphere is not subjected to modification treatment.

[0064] Example

[0065] Example 1: A lithium manganese iron phosphate positive electrode material is prepared according to the following method:

[0066] Preparation of ferromanganese phosphate precursor:

[0067] Phosphoric acid, manganese sulfate and 60 wt % of ferric nitrate are added to deionized water, and the solid content is controlled to be 40% to prepare a premixed solution;

[0068] Add the modified hollow carbon microspheres and sodium dodecylbenzene sulfonate prepared in Preparation Example 1 to the premixed solution, raise the temperature to 80° C., stir and react for 5 hours, then filter, wash and dry to obtain a pre-reactant;

[0069] The pre-reactant was dispersed in deionized water, the solid content was controlled to be 50%, the remaining amount of ferric nitrate was added, the temperature was raised to 65°C in a nitrogen atmosphere, and the mixture was stirred and mixed for 2 hours, and then washed, dried and calcined at 300°C to obtain a manganese iron phosphate precursor.

[0070] The amount of phosphoric acid added is 1 mol; the molar ratio of phosphoric acid, manganese sulfate and ferric nitrate is 1:0.4:0.6; the amount of modified hollow carbon microspheres prepared in Preparation Example 1 added is 15% of the total mass of phosphoric acid, manganese sulfate and ferric nitrate; the amount of sodium dodecylbenzene sulfonate added is 5% of the total mass of phosphoric acid, manganese sulfate and ferric nitrate.

[0071] Preparation of lithium manganese iron phosphate positive electrode material:

[0072] 100 g of the above-obtained ferromanganese phosphate precursor, lithium hydroxide and 8 g of sucrose were mixed and prepared into a slurry with deionized water. The solid content of the slurry was 50%;

[0073] The obtained slurry is ground and spray-dried, then sintered at 750°C, and finally crushed to obtain the lithium manganese iron phosphate positive electrode material.

[0074] The molar ratio of lithium hydroxide to phosphoric acid is 1:1.

[0075] Example 2, a lithium manganese iron phosphate positive electrode material, is different from Example 1 only in that the molar ratio of phosphoric acid, manganese sulfate and ferric nitrate is 1:0.3:0.7; the molar ratio of lithium hydroxide to phosphoric acid is 0.95:1; and the added amount of sucrose is 5g.

[0076] Example 3, a lithium manganese iron phosphate positive electrode material, is different from Example 1 only in that the molar ratio of phosphoric acid, manganese sulfate and ferric nitrate is 1:0.5:0.5; the molar ratio of lithium hydroxide to phosphoric acid is 1.1:1; and the added amount of sucrose is 10g.

[0077] Example 4, a lithium manganese iron phosphate positive electrode material, is different from Example 1 only in that the added amount of the modified hollow carbon microspheres prepared in Preparation Example 1 is 10% of the total mass of phosphoric acid, manganese sulfate and ferric nitrate.

[0078] Example 5, a lithium manganese iron phosphate positive electrode material, is different from Example 1 only in that the added amount of the modified hollow carbon microspheres prepared in Preparation Example 1 is 20% of the total mass of phosphoric acid, manganese sulfate and ferric nitrate.

[0079] Example 6, a lithium manganese iron phosphate positive electrode material, differs from Example 1 only in that the modified hollow carbon microspheres prepared in Preparation Example 1 are replaced with an equal amount of modified hollow carbon microspheres prepared in Preparation Example 2; and the amount of sodium dodecylbenzene sulfonate added is 3% of the total mass of phosphoric acid, manganese sulfate and ferric nitrate.

[0080] Example 7, a lithium manganese iron phosphate positive electrode material, differs from Example 1 only in that the modified hollow carbon microspheres prepared in Preparation Example 1 are replaced with an equal amount of modified hollow carbon microspheres prepared in Preparation Example 3; the amount of sodium dodecylbenzene sulfonate added is 6% of the total mass of phosphoric acid, manganese sulfate and ferric nitrate.

[0081] Example 8, a lithium manganese iron phosphate positive electrode material, is different from Example 1 only in that the modified hollow carbon microspheres prepared in Preparation Example 4 are used to replace the modified hollow carbon microspheres prepared in Preparation Example 1.

[0082] Example 9, a lithium manganese iron phosphate positive electrode material, is different from Example 1 only in that the modified hollow carbon microspheres prepared in Preparation Example 1 are replaced by an equal amount of modified hollow carbon microspheres prepared in Preparation Example 5.

[0083] Example 10, a lithium manganese iron phosphate positive electrode material, is different from Example 1 only in that the added amount of the modified hollow carbon microspheres prepared in Preparation Example 1 is 5% of the total mass of phosphoric acid, manganese sulfate and ferric nitrate.

[0084] Example 11, a lithium manganese iron phosphate positive electrode material, is different from Example 1 only in that the added amount of the modified hollow carbon microspheres prepared in Preparation Example 1 is 25% of the total mass of phosphoric acid, manganese sulfate and ferric nitrate.

[0085] Example 12, a lithium manganese iron phosphate positive electrode material, is different from Example 1 only in that the molar ratio of phosphoric acid, manganese sulfate and ferric nitrate is 1:0.2:0.8.

[0086] Example 13, a lithium manganese iron phosphate positive electrode material, is different from Example 1 only in that the molar ratio of phosphoric acid, manganese sulfate and ferric nitrate is 1:0.7:0.3.

[0087] Comparative Example

[0088] Comparative Example 1, a lithium manganese iron phosphate positive electrode material, is different from Example 1 only in that the modified hollow carbon microspheres prepared in Preparation Example 1 are replaced by an equal amount of modified hollow carbon microspheres prepared in Preparation Example 6.

[0089] Comparative Example 2, a lithium manganese iron phosphate positive electrode material, is different from Example 1 only in that the modified hollow carbon microspheres prepared in Preparation Example 1 are replaced by an equal amount of modified hollow carbon microspheres prepared in Preparation Example 7.

[0090] Comparative Example 3, a lithium manganese iron phosphate positive electrode material, is different from Example 1 only in that the modified hollow carbon microspheres prepared in Preparation Example 1 are replaced by an equal amount of hollow carbon microspheres prepared in Preparation Example 8.

[0091] Comparative Example 4 is a lithium iron manganese phosphate positive electrode material, which is different from Example 1 only in that the modified hollow carbon microspheres prepared in Preparation Example 1 are not added during the preparation of the lithium iron manganese phosphate precursor.

[0092] Performance testing

[0093] Sample preparation:

[0094] The lithium manganese iron phosphate positive electrode material, the conductive agent Super-p and the binder polyvinylidene fluoride (PVDF) solution (5wt% dissolved in N-methylpyrrolidone) with a mass ratio of 8:1:1 were weighed and placed in a homogenization tank, and an appropriate amount of N-methylpyrrolidone was added thereto. After being treated with a high-speed homogenizer for several minutes, a uniform black slurry was obtained. The slurry was poured on a flat aluminum foil (14μm), flattened with the 400μm surface of a four-sided film maker, placed in an 80℃ forced air drying oven for 4 h, and then taken out and sliced ​​with a button battery puncher to obtain a pole piece (diameter 14 mm), and the pole piece was rolled and placed in a vacuum tube at 120℃ for 4 h.

[0095] A CR2025 button cell was made by using a metallic lithium sheet as the negative electrode, a polypropylene microporous membrane (Celgard 2300) as the separator, and 1 mol / L lithium hexafluorophosphate (ethylene carbonate: dimethyl carbonate: ethyl methyl carbonate = 1:1:1) as the electrolyte. The cells were sealed in an argon-filled glove box.

[0096] 1. Manganese dissolution performance test: Fully charge at 0.1 times rate, then stand at 60℃ for 7 days, then dissolve the metal lithium sheet in 0.1mol / L hydrogen chloride aqueous solution, and test the content of manganese ions in hydrogen chloride aqueous solution by atomic absorption spectrometry to characterize the dissolution of manganese. The test results are shown in Table 1.

[0097] 2. Electrochemical performance test:

[0098] (1) At room temperature, the voltage range is 2.5 to 4.3 V, and the battery capacity is tested at a rate of 0.1C;

[0099] (2) At room temperature, the voltage range is 2.5-4.3 V, and the charge and discharge cycle is repeated 300 times at a rate of 1C. The capacity retention rate after the cycle is tested.

[0100] The above test results are shown in Table 2.

[0101]

[0102]

[0103] According to Table 1 and Table 2, in combination with Example 1 and Example 2 to Example 7, it can be seen that there is no significant difference in the content of manganese ions in the aqueous solution of hydrogen chloride, the specific capacity, and the cycle capacity retention rate of Example 2 to Example 7 compared with Example 1, indicating that there is no significant difference in the manganese dissolution performance and cycle performance of Example 2 to Example 7 compared with Example 1. The reason is that compared with Example 1, Example 2 to Example 7 only changes the raw materials and their proportions within the required range, which has little effect on the electrochemical performance of the positive electrode material.

[0104] In combination with Example 1, Example 8, Example 9 and Comparative Example 2, it can be seen that the content of manganese ions in the aqueous solution of hydrogen chloride in Example 8, Example 9 and Comparative Example 2 is increased compared to Example 1, and the specific capacity and cycle capacity retention rate are decreased, among which Comparative Example 2 changes most significantly. The reason is that the content of thiol groups on the surface of the modified hollow carbon microspheres is reduced in Example 8, and the valence control ability of manganese ions and iron ions is reduced, and it cannot be completely reduced, and the divalent state is always kept unified. The trivalent manganese ions that have not been reduced are prone to valence disproportionation during the charge and discharge process, thereby causing lattice distortion of the positive electrode material, resulting in the dissolution of manganese and the decline of cycle performance. There is no thiol group on the surface of the hollow carbon microspheres in Comparative Example 2, and the corresponding performance decline is more obvious. In Example 9, the content of thiol groups is increased, and the excess thiol groups will compete for metal ions, affect the uniform distribution and crystallization process of manganese iron phosphate, and there is also the possibility of lattice distortion, thereby reducing the performance of the positive electrode material.

[0105] In combination with Example 1, Example 10, Example 11 and Comparative Example 4, it can be seen that in Example 10, Example 11 and Comparative Example 4, compared with Example 1, the content of manganese ions in the aqueous solution of hydrogen chloride is increased, and the specific capacity and cycle capacity retention rate are decreased, wherein Comparative Example 4 changes most significantly, and the dissolution phenomenon of manganese is significant. The reason may be that the amount of modified hollow carbon microspheres added is reduced in Example 10. In addition to the reduction of the skeleton structure of fixed manganese ions and iron ions, the conductivity of the material is also reduced, the number of three-dimensional conductive networks is reduced, and the diffusion rate of lithium ions and the transmission rate of free electrons are affected, resulting in a decrease in the specific capacity of the material. In Comparative Example 4, modified hollow carbon microspheres are not used as carrier materials for ferromanganese phosphate precursors, and manganese will be dissolved in large quantities, and the valence disproportionation that occurs will cause lattice distortion of the positive electrode material during the charge and discharge cycle, resulting in a significant decrease in material cycle performance and a significant decrease in specific capacity. The number of modified hollow carbon microspheres is increased in Example 11, which is not conducive to the close and uniform distribution between ferromanganese phosphate particles, and will reduce the specific capacity of the positive electrode material.

[0106] Combining Example 1, Example 12 and Comparative Example 13, it can be seen that the content of manganese ions in the aqueous solution of hydrogen chloride is increased, and the specific capacity and cycle capacity retention rate are decreased in Example 12 and Comparative Example 13 compared with Example 1. The reason is that the molar ratio of manganese / iron is changed in Example 12 and Example 13, wherein the manganese content is reduced in Example 12, which will cause the specific capacity of the material to decrease, and the manganese content is increased in Example 13, and the cycle performance will decrease accordingly.

[0107] In combination with Example 1, Comparative Example 1 and Comparative Example 3, it can be seen that the content of manganese ions in the aqueous solution of hydrogen chloride in Comparative Example 1 and Comparative Example 3 is significantly improved compared with Example 1, and the specific capacity and cycle capacity retention rate are significantly reduced. The reason is that there is no layer of polypyrrole deposited on the surface of the modified hollow carbon microspheres in Comparative Example 1. On the one hand, it will reduce the attraction of the modified hollow carbon microspheres to metal ions, and it is difficult for manganese iron phosphate to grow completely inside or on the surface of the modified hollow carbon microspheres. On the other hand, it will reduce the binding force between the thiol group and the hollow carbon microspheres, and will reduce the reinforcement of the skeleton structure of the hollow carbon microspheres. The stability of the material is also reduced, and the dissolution rate of manganese will be increased, and the cycle performance of the positive electrode material will be reduced. In Comparative Example 3, the hollow carbon microspheres have not been modified, not only lacking the attraction and reinforcement of polypyrrole to metal ions, but also affecting the uniformity of the valence states of manganese ions and iron ions, thereby causing the dissolution of manganese to intensify, and the cycle performance is reduced.

[0108] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0109] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a ferromanganese phosphate precursor, characterized in that: The process steps include: S101. Adding a phosphorus source, a manganese source and a portion of an iron source to deionized water to prepare a premix, wherein the portion of the iron source is 50 to 60% of the total mass of the iron source; S102. Adding modified hollow carbon microspheres and a dispersant to the premixed solution, raising the temperature to 70 to 80° C., stirring the reaction for 4 to 6 hours, filtering, washing and drying to obtain a pre-reactant; S103. The pre-reactant is dispersed in deionized water, the remaining iron source is added, the temperature is raised to 60 to 70 ° C in a nitrogen atmosphere, stirred and mixed for 2 to 3 hours, and then washed, dried and calcined to obtain a manganese iron phosphate precursor; The surface of the modified hollow carbon microspheres contains mercapto groups.

2. The method for preparing the ferromanganese phosphate precursor according to claim 1, characterized in that: The molar ratio of the phosphorus source, manganese source and iron source is 1: (0.3-0.5): (0.5-0.7).

3. The method for preparing the ferromanganese phosphate precursor according to claim 1, characterized in that: The added amount of the modified hollow carbon microspheres is 10-20% of the total mass of the phosphorus source, the manganese source and the iron source.

4. The method for preparing the ferromanganese phosphate precursor according to claim 1, characterized in that: The raw materials of the modified hollow carbon microspheres include hollow carbon microspheres, pyrrole monomers and mercapto acid in a mass ratio of 1: (0.3-0.5): (0.05-0.1).

5. The method for preparing the ferromanganese phosphate precursor according to claim 4, characterized in that: The mercapto acid includes a combination of one or more of thioglycolic acid, mercaptopropionic acid and 6-mercaptohexanoic acid.

6. The method for preparing the ferromanganese phosphate precursor according to claim 4, characterized in that: The modified hollow carbon microspheres are prepared according to the following method: hollow carbon microspheres are added to a solvent, the pH value of the solution is adjusted to 2-3, and after uniform dispersion, pyrrole monomer and mercapto acid are added, and the mixture is stirred and mixed at 0-25° C., an initiator is added, and the stirring reaction is continued for 6-8 hours, and then the modified hollow carbon microspheres are obtained by vacuum filtration, washing and drying.

7. A ferromanganese phosphate precursor, characterized in that: The method for preparing the ferromanganese phosphate precursor according to any one of claims 1 to 6 is used to prepare the ferromanganese phosphate precursor.

8. A method for preparing a lithium manganese iron phosphate positive electrode material, characterized in that: The process steps include: S201. The lithium source, the carbon source and the ferromanganese phosphate precursor according to claim 7 are mixed and configured with deionized water to form a slurry; S202. Grind and spray-dry the obtained slurry, then sinter it at a high temperature of 600-800° C., and finally crush it to obtain the lithium manganese iron phosphate positive electrode material.

9. The method for preparing lithium iron manganese phosphate positive electrode material according to claim 8, characterized in that: The molar ratio of the lithium source to the phosphorus source in step S101 is (0.95-1.1):1; the added amount of the carbon source is 5-10% of the mass of the ferromanganese phosphate precursor.

10. A lithium manganese iron phosphate positive electrode material, characterized in that: The material is prepared according to the method for preparing the lithium manganese iron phosphate positive electrode material according to any one of claims 8 to 9.

Citation Information

Patent Citations

  • Preparation method of hollow bowl-shaped carbon-based metal oxide composite material

    CN104241602A

  • Spherical LiMnFeVPO4 / C composite positive electrode material and preparation method and application thereof

    CN115548293A